ATL, BTL, TTL Advertising - Udod, Kateryna (My University, 2014)
ATL, BTL and TTL are the acronym for Above The Line, Below The Line and Through The Line advertising strategies for promotion and penetrating the potential market to reach to its maximum customer. ATL includes Television, Radio and Print media like magazines, Newspapers etc. and it covers a lot of mass through its huge reach.
Keywords: business; strategies; advertising; реклама; бізнес; стратегії